FACTORS RELATED TO INHIBITIONS IN HEALING OF OPERATIVE WOUNDS AT HERMINA OPI MOTHER AND CHILDREN'S HOSPITAL, JAKABARING, 2022 - Larasati, Larasati; Intan, Intan; Alkhusari, Alkhusari; Jaya, Indra Frana (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Surgical site infection (SSI) is an infection at the surgical site which is one of the main complications of surgery which increases morbidity and costs of treating patients in hospital, and even increases patient mortality. Wounds are the main route for infection/reinfection during the healing process. This often occurs in oral wounds caused by increased formation of plaque and food debris. Data from the operating room at the Hermina Opi Jakabaring MOTHER AND CHILDREN'S HOSPITAL in the last 6 months of 2022 recorded that there were 1307 surgical patients, 43.56% of patients who experienced long days in the healing process of surgical wounds were in this age group and 56.93 patients experienced long days in the healing process. Surgical wounds are in the nutritional group and only 1% of patients who experience a long healing process in surgical wounds are in the infection group.